1998
DOI: 10.1038/sj.cdd.4400362
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of Fas and Fas-ligand on the surface of influenza virus-infected cells

Abstract: Influenza virus-infected cultured cells undergo apoptosis after an increment of Fas (APO-1/CD95) on the cell surface. By flow cytometry, cell surface Fas-ligand was detected in virusinfected cells with a time course similar to that of Fas. Moreover, Fas and Fas-ligand were co-expressed in those cells. The mode of induction, however, appeared to be distinct for the two proteins. Influenza virus infection induced the externalization of phosphatidylserine on the cell surface at the early stage of apoptosis, an ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 19 publications
2
61
0
Order By: Relevance
“…Evidence is accumulating to support the idea that apoptosis and inflammation are linked in influenza infection (3,15,35,36,51,52). For example, it has been shown previously that a proinflammatory cytokine, interleukin-8, is secreted upon the induction of apoptosis in bronchiolar epithelial cells by Fas ligation (7,13,15,21).…”
Section: Discussionmentioning
confidence: 93%
“…Evidence is accumulating to support the idea that apoptosis and inflammation are linked in influenza infection (3,15,35,36,51,52). For example, it has been shown previously that a proinflammatory cytokine, interleukin-8, is secreted upon the induction of apoptosis in bronchiolar epithelial cells by Fas ligation (7,13,15,21).…”
Section: Discussionmentioning
confidence: 93%
“…47 Fujimoto and coworkers 48 showed that influenza infection induces apoptosis via activation of pathways mediated by the Fas-Fas ligand complex in Hela cells. Fas and Fas ligand then activate a caspase cascade and induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the death receptor-mediated apoptosis pathway induced by influenza infection has been extensively studied Wada et al, 1995;Fujimoto et al, 1998), little is known about the potential participation of the mitochondriamediated apoptosis pathway during influenza-induced cell death. Although PK-15 cells are not commonly used for swine influenza virus replication, our results shown in Figure 1 demonstrated that PK-15 cell was shown to fully support SIV replications.…”
Section: Discussionmentioning
confidence: 99%
“…Both cellular and viral factors are involved in this process, which may also depend on the cell type. Although influenza virus-induced apoptosis is inhibited by Bcl-2 (Olsen et al, 1996), v-FLIP, and crmA (Takizawa et al, 1999), the best characterized pathway of influenzainduced apoptosis is that activation of receptor-mediated signaling is associated with the activation of caspase-8 (death receptor pathway) Fujimoto et al, 1998). However, although the Bcl-2 family is associated with apoptosis in various viral infections (Conti et al, 1998;Duncan et al, 1999;Lewis et al, 1999), there have been few reports regarding the activation of members of the Bcl-2 family by the influenza virus.…”
Section: Introductionmentioning
confidence: 99%